Cutting cocoa, Trinidad - (:unkn) unknown (Thomas Studio, Trinidad, 2010)
A picture of a group of labourers breaking the cocoa pods to get the cocoa beans which are then placed in large baskets. Postcard numbered 3731.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cocoa--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Working class--Trinidad and Tobago; Cocoa trade--Trinidad and Tobago; Cocoa processing--Trinidad and Tobago